La violencia en la tierra. Una mirada a las relaciones de poder en Guatemala desde las fosas de exhumación vacías - Clara Duterme (Nuevo mundo - Mundos Nuevos, 2021)
In a national context where the history of the armed conflict (1960-1996) and the violence resulted in 200 000 victims of massacre and forced displacement, most of them Indigenous) have been historically ignored, exhumations have become a key element for the victim recognition in Guatemala. The uncovering of the bones constitutes evidence of the violence, while their transformations (exhumation, identification and re-inhumation) affects the social and geographical landscape. Less attention has been paid to those cases where no remains appear. Such cases allow us to analyse how silenced violence lingers in the daily lives of survivors, rooted in the land as it is a marker of the social inequalities affecting both the living and the dead.